The Effect of Work Place Spirituality, Self Efficacy and Knowledge Sharing towards Academics Research Productivity - Michael Ananda; Hafid Abbas; Mahmuddin Yasin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to find out more about how self-efficacy and workplace spirituality can have a direct or indirect influence on lecturers who consider themselves productive in conducting research, through knowledge sharing as a mediator that should be considered as a critical supporting element. Knowledge sharing behavior has been proven by previous experts to be able to contribute to the creation of new knowledge and collective intelligence that can increase individual and group productivity. Self-efficacy in this study consists of knowledge self-efficacy – which includes the willingness for lecturers to share knowledge both explicitly and tacitly with colleagues and also the institution where they are sheltered – and research self-efficacy, which influences lecturers to be more productive in conducting research. In the work environment at higher education institutions, spirituality in the workplace describes the daily life of lecturers as educators who feel that their work provides a positive boost from a sense of self-worth, and meaning in their work. This research was conducted at two higher education institutions in the city of Baubau, Southeast Sulawesi, namely the University of Dayannu Ikhsanuddin and the University of Muhammadiyah Buton. The sample included 194 permanent lecturers, and the Partial Least Squares approach through SmartPLS was used as an analytical tool. The results show that knowledge self-efficacy and spirituality in the workplace have a direct and significant effect on knowledge sharing. Knowledge sharing and research self-efficacy also have a direct effect on research productivity. In addition, knowledge self-efficacy and workplace spirituality have a significant indirect effect on lecturer research productivity.